The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms9010050
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insight into Pediococcus acidilactici HN9, a Potential Probiotic Strain Isolated from the Traditional Thai-Style Fermented Beef Nhang

Abstract: Pediococcus acidilactici HN9 is a beneficial lactic acid bacterium isolated from Nhang, a traditional Thai-style fermented beef. In this study, the molecular properties of P. acidilactici HN9 were characterized to provide insights into its potential probiotic activity. Specifically, this work sought to report the complete genome of P. acidilactici HN9 and perform a comparative genome analysis with other bacterial strains belonging to the genus Pediococcus. Genomic features of HN9 were compared with those of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…The P. acidilactici ST31BZ genome showed similar values of size, GC content, number of predicted proteins and ribosomal operons as other P. acidilactici strains 10,12 . Detected CRISPR systems are similar to previously described in P. acidilactici HN9 13 . A small plasmid-encoded bacteriocin (~ 9 kb) was detected, such as found in pSMB74 14 and pCP289 15 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The P. acidilactici ST31BZ genome showed similar values of size, GC content, number of predicted proteins and ribosomal operons as other P. acidilactici strains 10,12 . Detected CRISPR systems are similar to previously described in P. acidilactici HN9 13 . A small plasmid-encoded bacteriocin (~ 9 kb) was detected, such as found in pSMB74 14 and pCP289 15 .…”
Section: Discussionsupporting
confidence: 62%
“…2a). The pST31BZ-1 plasmid was similar to pHN9-1 (BLASTn, Identity: 98.19%; Coverage: 58%), a 42,239 bp plasmid found in P. acidilactici HN9 isolated from the Traditional Thai-Style Fermented Beef Nhang (Surachat et al, 2021). No antibiotic resistance genes were predicted using ARIBA in the genome or plasmids of strain ST31BZ, however, we were able to predict the following resistance genes using the KEGG GhostKoala automatic annotation pipeline: Lantibiotic tranporter system (NisE/F/G), Lincosamide and streptogramin A resistance (Lsa), Beta lactamase class A (PenP), Cationic antimicrobial P. acidilactici ST31BZ genome presented genes coding for several sugar transporters such as sucrose, maltose/glucose and cellobiose, and is likely able to degrade them all to lactate and acetate.…”
Section: Pediococcus Acidilactici St31bz Genome Characterizationmentioning
confidence: 88%
“…This analysis clarified the frequency of bacteriocin-encoding genes in Weissella spp. We found that only a few bacterial strains in the genus encode ribosomally synthesized antibacterial peptides, while LAB in other genera encode a larger diversity of bacteriocin-encoding genes: for example, Pediococcus ( Jiang et al, 2020 ; Surachat et al, 2021b ), Lactobacillus ( Kaskoniene et al, 2017 ; Surachat et al, 2021a ), and Enterococcus ( Nes et al, 2007 ; Lopez-Cuellar et al, 2016 ). Even though bacteriocins are a crucial biological tool for inhibiting pathogens and other microorganisms, most Weissella spp.…”
Section: Resultsmentioning
confidence: 96%
“…The assembly process was then performed by Unicycler v0.4.7 ( Wick et al, 2017 ) using both the short-read and long-read sequences. We then scanned for a small plasmid that could be absent from the assembly as described previously ( Surachat et al, 2021a , b ). Briefly, we mapped short-read sequences to draft assembly and extracted all unmapped reads to perform de novo assembly with spades v3.12 ( Bankevich et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the bacteriocin enterolysin is detected in many strains of this analysis and is known to degrade bacterial cell walls and be produced by bacteria of genera Enterococcus , Lactobacillus , Streptococcus , and Pediococcus , showing potential for inhibition of enterococci, pediococci, lactococci, and lactobacilli [60] . This bacteriocin belongs to class III, which are thermostable peptides with a broad inhibitory spectrum [61] .…”
Section: Discussionmentioning
confidence: 97%